Experience of using chemotherapy treatment for the first recurrence of ovarian cancer - V. N. Zhurman (Сибирский онкологический журнал)
Background. The main goal of treating patients with recurrent ovarian cancer is to prolong life and improve its quality. Approaches to the treatment of recurrent ovarian cancer have changed over the past decade. The choice of antitumor drug therapy is determined by the duration of platinum-free interval and the use of targeted therapy with bevacizumab or olaparib. Treatment regimens for relapses are not unified and treatment outcomes are contradictory. Aim: to analyze treatment outcomes of different chemotherapy regimens in patients with the first recurrence of ovarian cancer, depending on the duration of platinum-free interval. Material and Methods. A retrospective analysis of the first recurrence of ovarian cancer in 446 patients treated at the Primorsky Regional Oncology Center in the period 2004–2021 was carried out. All patients were divided into two groups depending on the treatment option for relapse: repeated cytoreduction followed by chemotherapy or only second-line chemotherapy, and into four groups depending on the chemotherapy regimens: 1 – platinum and taxane agents; 2 – platinum and taxane agents with bevacizumab; 3 – platinum agents and non-taxane agents with bevacizumab; 4 – monotherapy with non-platinum agents with bevacizumab. Results. Significant advantages in progression-free survival after second-line chemotherapy (PFS-2) were observed in patients with platinum-resistant relapse after the 4th chemotherapy regimen. Patients with platinum-sensitive relapse had the best treatment outcomes after the 3rd chemotherapy regimen and repeated cytoreduction followed by chemotherapy with a platinum-free interval of 6–12 months and 12–24 months with any platinum-containing chemotherapy regimen. In the platinum-free interval of more than 24 months, significant benefits were observed with a combination of platinum and taxane agents + bevacizumab. In the group of patients without surgery, there were significant benefits in all three intervals when prescribing a combination of platinum and non-oxane agents ± bevacizumab. There was a tendency to increase PFS-2 in patients with low-grade serous ovarian carcinoma compared with patients with high-grade serous carcinoma. The best rates of relapse-free survival were noted with maintenance therapy with olaparib. Conclusion. In patients with localized recurrence of ovarian cancer and a platinum-free interval of more than 6 months, it is advisable to perform repeated cytoreduction followed by chemotherapy, taking into account the duration of the platinum-free interval. The administration of PARP inhibitors in the maintenance therapy of platinum-sensitive recurrence of ovarian cancer improves treatment results.